The Dialectics of Aesthetics and Philosophy in Tandang Mendet Dance: Analysis and Its Implications for Cultural Education - Rifki Ayu Rosmita; Reni Anggraeni; Yuni Iriani Suganda Putri (Journal La Edusci, 2026)
This study examines the relationship between aesthetic structures and philosophical meanings in Tandang Mendet Dance as a cultural practice of the Sasak community. Departing from the prevalent tendency to separate aesthetics from meaning in traditional art studies, this research employs an interpretive qualitative approach, integrating semiotic analysis, symbolic anthropology, and the sociology of art. Data were collected through observation, interviews, and documentation of Tandang Mendet performances at the Sembalun Mountain Festival 2025. The findings reveal that the aesthetic structure comprising repetitive movement patterns, collective synchronization, the use of properties, and musical rhythm functions as an operational system in the articulation of values. The philosophy of Lombok Mirah Sasak Adi, particularly the value of honesty, is not verbally represented but is internalized through consistent and coordinated performative practices. The analysis demonstrates a dialectical relationship between aesthetics and philosophy, in which form not only represents meaning but also produces and reproduces it within a dynamic social context. The study further highlights that traditional arts can function as an experiential medium of cultural education, while simultaneously confronting challenges of commodification and the transformation of meaning in the context of globalization.